INTERACTIONS BETWEEN DISSOLVED SILICA AND CARBONATE MINERALS: AN EXPERIMENTAL STUDY AT 25-50°C - Klein R.T.; Walter L.M. (My University, 1995)
Replacement of carbonate minerals by silica polymorphs in marine and meteoric environments is a common early diagenetic feature of sedimentary rocks. Although relatively few experimental investigations have been made of interactions between carbonate minerals and dissolved SiO2 at moderate temperatures, available data suggest that silica uptake onto carbonate surfaces can be significant. We present results of experiments conducted between 25° and 50°C of the uptake of aqueous SiO2 from artificial seawater (Mg-Na-Cl-Ca-HCO3, I = 0.7) and meteoric-type (CaCl2-Na2CO3, I < 0.1) solutions onto well-characterized Ca-Mg-carbonates. Silica concentrations ranged from 1.5 to 3.0 mM, a reasonable upper limit for natural diagenetic waters. Dissolved silica-carbonate mineral interactions were investigated under three experimental conditions: (1) in solutions near equilibrium with respect to calcite; (2) in calcite-seeded precipitation experiments at fixed degrees of calcite supersaturation; and (3) during closed-system, dissolution-precipitation of metastable carbonate minerals (aragonite and 18 mole% Mg-calcite) to low-Mg calcite (LMC).In artificial seawater (ASW) maintained near equilibrium with respect to calcite at variousPCO2 -values, silica uptake from solution onto calcite surfaces (# 1-15 μmol Si/gram seed) was irreversible and strongly time-and pH-dependent...

Replacement of carbonate minerals by silica polymorphs in marine and meteoric environments is a common early diagenetic feature of sedimentary rocks. Although relatively few experimental investigations have been made of interactions between carbonate minerals and dissolved SiO2 at moderate temperatures, available data suggest that silica uptake onto carbonate surfaces can be significant. We present results of experiments conducted between 25° and 50°C of the uptake of aqueous SiO2 from artificial seawater (Mg-Na-Cl-Ca-HCO3, I = 0.7) and meteoric-type (CaCl2-Na2CO3, I < 0.1) solutions onto well-characterized Ca-Mg-carbonates. Silica concentrations ranged from 1.5 to 3.0 mM, a reasonable upper limit for natural diagenetic waters. Dissolved silica-carbonate mineral interactions were investigated under three experimental conditions: (1) in solutions near equilibrium with respect to calcite; (2) in calcite-seeded precipitation experiments at fixed degrees of calcite supersaturation; and (3) during closed-system, dissolution-precipitation of metastable carbonate minerals (aragonite and 18 mole% Mg-calcite) to low-Mg calcite (LMC).In artificial seawater (ASW) maintained near equilibrium with respect to calcite at variousPCO2 -values, silica uptake from solution onto calcite surfaces (# 1-15 μmol Si/gram seed) was irreversible and strongly time-and pH-dependent. The rate of uptake was greatest in the first 5 hr and in solutions of lower pH (higher PCO2). Silica uptake was only nominally dependent on solution [Mg] and temperature over the range studied. Silica uptake was greater in ASW than in otherwise comparable experiments conducted in low-ionic-strength solutions. Controlled calcite precipitation rates were unaffected by the adsorption of silica. During recrystallization of aragonite and Mg-calcite in low-ionic-strength solutions, silica uptake (1-6 μmol g-1) was similar to values from near-equilibrium experiments for synthetic calcite in ASW. Experimental Si adsorption values were comparable to Si adsorption values determined for modern metastable sediments (3-4 μmol g-1).Despite considerable variation in the experimental carbonate equilibrium-disequilibrium, mineralogy and solution chemistry, Si uptake at near-surface and moderate burial conditions (25-50°C) was limited to # 15 μmol g-1 Si even in solutions maintained near opal-CT saturation over a period of days to weeks.